Vpliv vadbe z vidnimi dražljaji na reakcijski čas pri športnikih - sistematični pregled literature - Zoroja, Monika (Šport (Ljubljana), 2021)
Athletes must be able to respond quickly to the visual stimulus. To improve motor respond to the visual stimulus, various methods including visual training can be used. The aim of this literature review was to analyze studies in which devices for visual reaction time assessment and training were used. A search was conducted using the databases PubMed, Cochrane Library, CINAHL and ScienceDirect. Five studies with control group were included in the review. Altogether four different devices and seven different reaction time measurement protocols have been used. Different types of visual training were performed, in majority in addition to the sport training. In four studies, statistically significant improvement in reaction time was reported after six weeks of visual training. Studies indicated a positive effect of visual training on the reaction time. Whether the skills of visual and motor systems acquired by training influence sport results and decrease injuries needs to be established in future.
Keywords: dinamični športi; dynamic sports; raziskave; reaction time; reakcijski čas; sport; svetlobni dražljaji; šport; vadba; vidni dražljaji; visual stimulus; visual stimulus devices; visual trainig